2018
DOI: 10.24874/ti.2018.40.01.01
|View full text |Cite
|
Sign up to set email alerts
|

The Accelerated Aging Effect of Salt Water on Lignocellulosic Fibre Reinforced Composites

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As a final point, the proposed AE methodology can be used as a capable tool for damage evaluation under low velocity impact events. Potential future studies include the validation of the same technique on green composites, given their recent rising interest from industry and literature [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…As a final point, the proposed AE methodology can be used as a capable tool for damage evaluation under low velocity impact events. Potential future studies include the validation of the same technique on green composites, given their recent rising interest from industry and literature [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms are (i) absorption of water molecules into the microscopic gaps of polymer chains, (ii) capillary movement of water molecules, due to insufficient wettability and impregnation, into the flaws and gaps at the interface of polymer and fibres and (iii) diffusion of water molecules into micro cracks in the matrix formed during the compaction process. 5,35 When composite materials are exposed to moisture, all three mechanisms come into play, but the cumulative effect can be readily simulated by merely considering only the diffusional mechanism. Diffusion behaviour in polymer composites can be characterised in general based on the relative mobility of polymer segments and the penetrant.…”
Section: Physical and Mechanical Characterizationmentioning
confidence: 99%
“…There exists some literature on the behaviour of NFRP composites in marine environment. [30][31][32][33][34] Fragassa et al 35 studied the effect of seawater absorption on the flexural properties of flax reinforced vinylester composites. They concluded that due to seawater aging, the flexural strength and modulus were reduced with an increase in flexural strain due to the reduction in the brittle nature of composites.…”
Section: Introductionmentioning
confidence: 99%
“…This effect of crack birth, growth and propagation is perhaps less evident in the case of other materials commonly used for small boats, such as wood or fiber reinforced plastics. These non-metallic materials, often snobbed when dealing with large shipbuilding, are supported by studies on the evaluation of the agging effect of salt water [3,4] and are getting back on track in considerations of unexpected advances in manufacturing [5] and their overall properties. These reinforcements might involve nanofibers [6], synthetic [7], natural [8,9] or hybrid fibers [10,11], representing a valid solutions for specific applications [12].…”
Section: Introductionmentioning
confidence: 96%